Verpleegster wat dink jy van die Doman-program - L.R. Uys (AOSIS, 1984)
Anyone working with mentally retarded children and their parents is regularly asked to voice an opinion on the Doman-program and every nurse should know enough about this to give such a professional opinion. The program is one of extremely intensive sensory and motor stimulation, based on an extensive evaluation of the individual child and provided by parents at home according to a very strict schedule. The program has met with much criticism including that the neurological development profile on which the originators base their program is unscientific, that the program may be harmful, that it is too rigid and demanding and that there is a lack of documentation to prove success. There are however positive aspects including the results which have been obtained, the direction it gives parents and the thorough evaluation of each child.